Dimethyl Sulfoxide Extract of Dianthus carmelitarum Induces S Phase Arrest and Apoptosis in Human Colon Cancer Cells. (3rd October 2019) - Turan, Ibrahim; Demir, Selim; Aliyazicioglu, Rezzan; Kilinc, Kagan; Ozer Yaman, Serap; Akbulut Cakiroglu, Kubra; Kanbolat, Seyda; Ayazoglu Demir, Elif; Mentese, Ahmet; Aliyazicioglu, Yuksel; Deger, Orhan
Abstract: Although several studies have investigated the cytotoxic effects of different Dianthus species, there has been only limited research into the cytotoxic effect of Dianthus carmelitarum. The purpose of this research was to evaluate the phenolic characterization and the cytotoxic effect of D. carmelitarum on human colon cancer (WiDr) cells and the possible mechanisms involved. Total polyphenolic contents (TPC) and phenolic characterization of the extract were evaluated using the Folin-Cioceltau method and reversed-phase high performance liquid chromatography (RP-HPLC), respectively. The cytotoxic activity of the extract was determined using the methylthiazolyldiphenyl-tetrazolium bromide (MTT) assay. The mechanism involved in the extract's cytotoxic effect was then evaluated in terms of apoptosis and the cell cycle using flow cytometry, while mitochondrial membrane potential (MMP) was investigated using the fluorometric method. The TPC value of the extract was 784.8 ± 40.3 mg gallic acid equivalent per 100 g sample, and sinapic acid and benzoic acid were detected as major phenolics in the extract. D. carmelitarum extract exhibited a selective cytotoxic effect (3.6-fold) on WiDr cells compared to normal colon cells. The extract induced cell cycle arrest at the S phase and apoptosis via reduced MMP in WiDr cells. Phytomedical and nutraceutical applications of D. carmelitarum may represent promising approaches in the treatment of cancer.